2017
DOI: 10.1038/icb.2017.24
|View full text |Cite
|
Sign up to set email alerts
|

Dominant TNFα and impaired IL‐2 cytokine profiles of CD4+ T cells from children with type‐1 diabetes

Abstract: Aberrantly activated CD4 T memory cells play a central role in the development of type-1-diabetes. Interleukin-7 promotes generation of autoimmune memory T cells and increased Interleukin-7 availability is associated with type-1-diabetes susceptibility. T-cell-mediated immune pathology at onset of type-1-diabetes is well defined, but characteristics of long-term symptomatic disease stages remain largely elusive. In the present study, memory CD4 T-cell activation and cytokine expression as well as sensitivity t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 50 publications
0
12
0
Order By: Relevance
“…Bian et al described a generally high‐activation pattern of memory T cells from T1D patients. Accordingly, we demonstrated that memory T cells from symptomatic T1D patients produced generally higher cytokine levels and were more sensitive to IL‐7‐mediated T cell costimulation . IL‐7 especially promoted the effector cytokines IFNγ and TNFα in these T1D patients, whereas relative IL‐2 production was lower as compared to healthy controls .…”
Section: Discussionmentioning
confidence: 82%
See 4 more Smart Citations
“…Bian et al described a generally high‐activation pattern of memory T cells from T1D patients. Accordingly, we demonstrated that memory T cells from symptomatic T1D patients produced generally higher cytokine levels and were more sensitive to IL‐7‐mediated T cell costimulation . IL‐7 especially promoted the effector cytokines IFNγ and TNFα in these T1D patients, whereas relative IL‐2 production was lower as compared to healthy controls .…”
Section: Discussionmentioning
confidence: 82%
“…Recently, we showed that IL‐7 differentially affected cytokine expressing T cell proportions of children with T1D in vitro . Hence, we compared IL‐7 effects on IFNγ, TNFα, and IL‐2 secretion of CD4 + and CD8 + T cells with differential IL‐7 serum levels.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations